Strengthening Organizational Resilience through Knowledge Management, Adversity Intelligence, and Work Motivation - Andi Hermawan; Muhamad Alwi; Soewarto Hardhienata (Golden Ratio of Social Science and Education, 2026)
Organizational resilience is a process carried out by organizational leaders in overcoming difficult situations by issuing appropriate policies and mobilizing all components of the organization and reformulating concrete positive steps in a short time so that the organization does not experience shocks and the organization's operational activities can run as they should. Educational institutions managed by the community as educational organizations face extraordinary challenges in the competition to survive and the slow pace of development due to educational policies. Therefore, research is needed to obtain information on variables related to increasing organizational resilience. This study aims to find strategies, methods and optimal solutions to increase organizational resilience through knowledge management, adversity intelligence and work motivation. This study uses a survey method with path analysis and the SITOREM method to analyze key indicators. Using smart PLS analysis to obtain the magnitude of the influence between the variables of knowledge management, adversity intelligence and work motivation on organizational resilience. Using SITOREM analysis, an optimal solution is obtained for increasing organizational resilience. This study provides recommendations for increasing organizational resilience that can be used as a reference for strategic decision making for school principals, the Education Office and the Ministry of Education.